Hubungan Antara Komunikasi Interpersonal dengan Organizational Citizenship Behaviour pada Karyawan PT. Kemilau Permata Sawit - Bella Moneta; Harry Theozard Fikri (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to determine the relationship between interpersonal communication with organizational citizenship behavior (OCB) on the employees of PT. Palm Gem Sheen. The independent variable in this study is interpersonal communication and the dependent variable is organizational citizenship behavior. Measuring instruments used in this research are interpersonal communication scale and organizational citizenship behavior scale. The sampling technique in this study was 98 employees of PT. Palm Gem Sheen. The validity and reliability test in this study used the Cronbach alpha technique. The results of the validity coefficient on the scale of interpersonal communication move from rix = 0.307 to rix = 0.73 with a reliability coefficient of α = 0.930 while on the scale of organizational citizenship behavior move from rix = 0.337 to rix = 0.734 with a reliability coefficient α = 0.931. Based on data analysis, obtained a correlation value of 0.324 with a significance level of 0.01, which means accepted. This shows that there is a significant relationship between interpersonal communication with organizational citizenship behavior among employees of PT. Palm Gem Sheen. The effective contribution of interpersonal communication variables to organizational citizenship behaviour by 10%